A Rare Case of Dextrocardia with Situs Inversus Totalis in a Patient of Diabetic Mother - Seyed Hassan Voshtani; Seyedeh Niloufar Seyed Saadat; Seyed Mohammad Seyed Saadat; Mojtaba Mehrdad; Hassan Moladoust; Ebrahim Nasiri (Negah Institute for Scientific Communication, 2013)
Infants of diabetic mothers are significantly at higher risk for major congenital malformations, with cardiovascular anomalies that is the most frequent. In this study, we presented a rare case of dextrocardia and situs inversus totalis (mirror-image dextrocardia) with multiple congenital heart anomalies who was born from a diabetic mother.